Mexican Murals in Times of Crisis - Campbell, Bruce, 1964- (Book collections on Project MUSE., 2003)
"Campbell brings all previous studies of Mexican muralism up to date by revealing the wealth of art that has flourished in the shadows of official recognition. His work shows that interpretations by art historians preoccupied with contemporary high art have been incomplete - and that a rich mural tradition still survives, and thrives, in Mexico."--Jacket.